Desacralizing The Past: The Liberal Approach to Islamic History - Hannan, Haukil (Faculty of Ushuluddin UIN Sunan Gunung Djati Bandung, 2024)
This research examines the approach of liberal thinkers towards the history of Islam, focusing on the articles published on the online platform Islamlib.com. The research problem is formulated as follows: How do the historical articles on Islam, particularly in terms of content and thematic choices, manifest themselves on Islamlib.com. Additionally, what criticisms regarding the history of Islam are developed by Islamlib.com, encompassing sources, methodology, and approaches. The research employs the historiographical method, analyzing themes, methods, data sources, and approaches through content analysis techniques. The findings indicate that the historical articles on Islamlib.com are crafted within the framework of Islamic history as part of world history and total history. This research argues that the historiography of liberal thinkers has reached a sophisticated level. The articles explore a variety of themes related to Islam, embracing a comprehensive view that goes beyond conventional narratives. The historiographical critiques offered by Islamlib.com extend to source reliability, methodological choices, and the adopted approaches. The methodology used in this study, content analysis, facilitates a thorough examination of the themes, methods, sources, and approaches present in the historical articles. The liberal historiography demonstrated on Islamlib.com reveals a nuanced and advanced understanding of Islamic history. This research contributes to the ongoing discourse on liberal perspectives in historiography, shedding light on the diverse themes and critical methodologies employed by liberal thinkers in shaping the narrative of Islamic history.